Towards an inclusive Parkinson's screening system - Geman, Oana; Sanei, Saeid; Chiuchisan, Iuliana; Graur, Adrian; Prochazka, Ales; Vysata, Oldrich (2014 18th International Conference on System Theory, Control and Computing (ICSTCC), 2014)
In this study, brain, and gait dynamic information were combined and used for diagnosis and monitoring of Parkinson's disease (the most important Neurodegenerative Disorder). Analysis of the information corresponding to a prescribed movement involving tremor, and the related changes in brain connectivity is novel and original. Analytically, developing a space-time nonlinear adaptive system which fuses brain and gait information algorithmically is proposed here for the first time. The overall dynamic system will be constrained by the clinical impressions of the patient symptoms embedded in a knowledge-based system. The entire complex constrained problem were solved to enable a powerful model for recognition and monitoring of Parkinson's disease and establishing appropriate rules for its clinical following up.